Debt dynamics with fixed issuance costs - Luca Benzoni; Lorenzo Garlappi; Robert S. Goldstein; Chao Ying (Federal Reserve Bank of Chicago, 2023)
We investigate equilibrium debt dynamics for a firm that cannot commit to a future debt policy and is subject to a fixed restructuring cost. We formally characterize equilibria when the firm is not required to repurchase outstanding debt prior to issuing additional debt. For realistic values of issuance costs and debt maturity, the no-commitment policy generates tax benefits that are similar to those obtained by a benchmark policy with commitment. For positive but arbitrarily small issuance costs, there are maturities for which shareholders extract essentially the entire claim to cash-flows.
Keywords: G12; G32; G33; 330; Capital structure; Debt dynamics; Commitment; Issuance costs; Debt maturity